Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is a nice problem on series convergence that I recently stumbled upon. Given a non-negative sequence of real numbers $(a_n)$ such that $$\sum_{n=1}^\infty a_n < \infty,$$ show that there exists a non-decreasing sequence of non-negative numbers $b_n$ such that $$b_n \to \infty \quad\text{ and } \quad \sum_{n=1}^\infty a_n b_n < \infty.$$ In other words, for every convergent series with non-negative terms, there is another convergent series with "substantially larger" terms.

I have a solution (see below), but maybe someone else has a different, simpler, and/or more elegant solution.

share|cite|improve this question
I see a series with terms $a_n$, and a summation over $k$. Shouldn't the terms be $a_k$ to match the summation? Or should the summation be $\displaystyle\sum_{n=1}^\infty$? I wonder what I'm missing here... – Matt Groff Oct 19 '12 at 23:53
Thanks Matt, fixed. – Lukas Geyer Oct 20 '12 at 1:30
You're welcome. This is quite an interesting find you have! – Matt Groff Oct 20 '12 at 16:52

By convergence of the series there exists a strictly increasing sequence of indices $(n_k)$ such that $$\sum_{n=n_k}^\infty a_n < 2^{-k}.$$ Then $$\sum_{k=1}^\infty \sum_{n=n_k}^\infty a_n < \sum_{k=1}^\infty 2^{-k} = 1.$$ Since series with non-negative terms can be reordered arbitrarily, we get $$1 > \sum_{n=1}^\infty \sum_{k\in I_n} a_n = \sum_{n=1}^\infty a_n b_n,$$ where $I_n = \{ k\in\mathbb{N}: n_k \le n \}$ and $b_n = \#I_n$ is the number of elements in $I_n$. We have that $n_k$ is strictly increasing and $n_k \to \infty$ as $k\to\infty$, so $b_n$ is non-decreasing and $b_n \to \infty$.

share|cite|improve this answer
+1 This is quite elegant in itself. – EuYu Oct 16 '12 at 0:51

Here is another way to do it. Let $$r_n = \sum_{k=n}^\infty a_k.$$ Then $(r_n)$ is a non-increasing sequence with $r_n \to 0$. We can assume $r_n >0$ for all $n$ (otherwise the claim is trivially true), and observe that $$\sqrt{r_n} - \sqrt{r_{n+1}} = \frac{r_n-r_{n+1}}{\sqrt{r_n} + \sqrt{r_{n+1}}} = \frac{a_n}{\sqrt{r_n} + \sqrt{r_{n+1}}}.$$ Define $$ b_n = \frac1{\sqrt{r_n} + \sqrt{r_{n+1}}}.$$ Then $(b_n)$ is a non-decreasing, positive sequence with $b_n \to \infty$, and $$\sum_{k=1}^n a_k b_k = \sum_{k=1}^n (\sqrt{r_k} - \sqrt{r_{k+1}})=\sqrt{r_1} - \sqrt{r_{n+1}},$$ so $$\sum_{k=1}^\infty a_k b_k = \sqrt{r_1} < \infty$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.